Differential Typology of Burnout in the Ukrainian Sample - Irkhin, Yurii B.; Chystovska, Yuliia; Pits, Iryna I.; Ryk, Hanna S.; Shyrokoradiuk, Liliia A. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Aim of study is a qualitative classification of manifestations of professional burnout based on quantitative indicators of exhaustion, cynicism and inefficiency. The paper substantiates the need to differentiate the symptoms of burnout from similar manifestations of professional maladjustment and personality disorders. The study involved 355 specialists of socionomic professions from different regions of Ukraine with work experience from 1 to 39 years (50.15% of men, 49.85% of women). Based on the cluster analysis of the three basic symptoms of burnout (exhaustion, cynicism, and depersonalisation), the groups of engaged and burned-out employees were identified, as well as qualitative and quantitative differences were showed. A comparative analysis of the groups was carried out for a number of additional diagnostic parameters: emotional attitude to work, the ratio of losses and gains of personal resources, the scale of psychological well-being, loyalty to the organisation. Typological profiles of 8 professional groups were created: effective employees ("engaged", "growing" and "taking" type), ineffective employees ("dependent" and "disengaged-relaxed" type), and three groups representing successive stages of burnout (accumulation of job stress, burnout itself and severe degree, accompanied by psychological distress in all spheres of life). The results allow us to conclude that particular symptoms of depersonalisation and reduction in personal achievements are not a sufficient basis for diagnosing burnout syndrome. The symptom of depersonalisation may be a manifestation of other professional deformations, not caused by burnout. Without combination with other parameters, the professional inefficiency is not a symptom of burnout; this is a common sign of insufficient development of competencies or an erroneous choice of the type of activity. Appropriate ways of organisational and psychological support are proposed.